2003
DOI: 10.1152/ajpheart.00844.2002
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of 5,6-EET on segmental pulmonary vasoactivity in the rabbit

Abstract: In the rabbit, 5,6-epoxyeicosatrienoic acid (EET) was reported both to dilate and to constrict pulmonary blood vessels. We propose that these seemingly contradictory results could be explained by differences in responses to 5,6-EET in large-conductance pulmonary arteries (PA) compared with smaller PA and resistance vessels. Thus we found that in rings of extralobar PA [>2-mm outside diameter (OD)], in which active tension had been increased with PGF(2alpha), 5,6-EET produced relaxation in a concentration- and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
27
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 27 publications
2
27
0
Order By: Relevance
“…Of these regioisomers, 5,6-EET has been reported to be the most abundant metabolite synthesized in rabbit lung (Zeldin et al, 1995), and it is the most potent pulmonary vasoconstrictor (Zhu et al, 2000). Although EETs relax most blood vessels in the systemic circulation, they contract intralobar segments of pulmonary arteries (PA) (Schwartzman et al, 1985;Zhu et al, 2000;Stephenson et al, 2003;Losapio et al, 2005) and increase pulmonary vascular resistance in isolated perfused lungs (Stephenson et al, 2003). Recently, the importance of this finding was illustrated in a report by Pokreisz et al (2006), who demonstrated that inhibition of epoxygenase activity significantly reduced acute hypoxic pulmonary vasoconstriction (HPV) and chronic hypoxia-induced pulmonary vascular remodeling in a mouse model of hypoxia-induced pulmonary hypertension.…”
mentioning
confidence: 99%
“…Of these regioisomers, 5,6-EET has been reported to be the most abundant metabolite synthesized in rabbit lung (Zeldin et al, 1995), and it is the most potent pulmonary vasoconstrictor (Zhu et al, 2000). Although EETs relax most blood vessels in the systemic circulation, they contract intralobar segments of pulmonary arteries (PA) (Schwartzman et al, 1985;Zhu et al, 2000;Stephenson et al, 2003;Losapio et al, 2005) and increase pulmonary vascular resistance in isolated perfused lungs (Stephenson et al, 2003). Recently, the importance of this finding was illustrated in a report by Pokreisz et al (2006), who demonstrated that inhibition of epoxygenase activity significantly reduced acute hypoxic pulmonary vasoconstriction (HPV) and chronic hypoxia-induced pulmonary vascular remodeling in a mouse model of hypoxia-induced pulmonary hypertension.…”
mentioning
confidence: 99%
“…The sEH inhibitors may also have detrimental effects on the pulmonary circulation, as EETs constrict the pulmonary vasculature [88][89][90][91] in most, but not all [92,93], animal models studied. The effects of EETs on the human pulmonary circulation remain unknown and future studies are needed to determine how sEH inhibition may alter vasomotor tone in this vascular bed.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of EET-induced vasodilation has been studied extensively and is dependent on the hyperpolarisation of vascular smooth muscle cells (Gebremedhin et al, 1992, Hecker et al, 1994, Campbell et al, 1996, Eckman et al, 1998, Morin et al, 2007a resulting from EETinduced opening of smooth muscle cell potassium channels (Campbell et al, 1996, Zou et al, 1996, Eckman et al, 1998, Gebremedhin et al, 1998, Hayabuchi et al, 1998, Morin et al, 2007a. Although EETs also reduce tension in non-resistant extralobar pulmonary artery (PA) segments (Stephenson et al, 1998, Stephenson et al, 2003, all four EET regioisomers have been observed to be vasoconstrictors in small-diameter intralobar PA segments in rabbits and rats (Yaghi et al, 2001. Because EETs also increase vascular resistance (and decrease compliance) in isolated perfused rabbit lungs (Stephenson et al, 2003), the predominant activity of EETs in lung vessels appears to be vasoconstriction.…”
Section: Role Of Cyp450-dependent Arachidonic Acid Metabolites In Pulmentioning
confidence: 99%
“…Although EETs also reduce tension in non-resistant extralobar pulmonary artery (PA) segments (Stephenson et al, 1998, Stephenson et al, 2003, all four EET regioisomers have been observed to be vasoconstrictors in small-diameter intralobar PA segments in rabbits and rats (Yaghi et al, 2001. Because EETs also increase vascular resistance (and decrease compliance) in isolated perfused rabbit lungs (Stephenson et al, 2003), the predominant activity of EETs in lung vessels appears to be vasoconstriction. These data are supported by the observation that inhibition of epoxygenase activity with specific pharmacological inhibitors attenuates PA tension to phenylephrine (Zhu et al, 2000a), suggesting that endogenous EETs participate in -adrenergic contraction of the pulmonary vasculature.…”
Section: Role Of Cyp450-dependent Arachidonic Acid Metabolites In Pulmentioning
confidence: 99%
See 1 more Smart Citation